Peningkatan Proses dan Hasil Belajar IPAS Siswa kelas VI Menggunakan Metode Kooperatif Scramble SDN 029/II Sungai Mancur - Weni Susilawati; Apdoludin Apdoludin; Megawati Megawati (CV. Master Literasi Indonesia, 2026)
By using the Scramble cooperative learning approach, this project seeks to enhance the Natural Sciences and Social Sciences (IPAS) learning process and results for sixth-grade students at SDN 029/II Sungai Mancur. minimal learning achievement just 40% of 20 students met the Learning Objective Competency Criteria (KKTP) and minimal student participation during learning activities serve as the study's backdrop. The planning, execution, observation, and reflection phases make up each of the two cycles of this Classroom Action Research (CAR) project. Twenty sixth-grade students served as the research subjects, and the goal was to apply the Cooperative Scramble approach to IPAS instruction. Learning outcome assessments, recording, and observation were among the methods used to gather data. Both quantitative and qualitative descriptive methodologies were used to analyse the data. The results showed an improvement in both the learning process and outcomes. In terms of process, teacher and student engagement increased from “adequate” in cycle I to “good” in cycle II. Regarding learning outcomes, the average student score increased from 69.4 in cycle I to 82.5 in cycle II, with the percentage of mastery rising from 55% to 90%. The Cooperative Scramble method proved effective in enhancing student activity and understanding of IPAS concepts